Transient Glutathione Depletion Determines Terminal Differentiation in HL-60 Cells. Issue 1 (2010) - Krance, Suzanne M.; Keng, Peter C.; Palis, James; Ballatori, Nazzareno
Abstract : To better define the role of glutathione (GSH) in cell differentiation, the present study measured GSH concentrations during terminal HL-60 cell differentiation, in the presence and absence of differentiation-inducing agents, and in the presence and absence of GSH altering agents. Interestingly, there was a small transient increase in intracellular GSH levels during dimethyl sulfoxide (DMSO) or 1α, 25-dihydroxyvitamin D3 (VD3) induced differentiation. This increase coincided with an increase in nitroblue tetrazolium (NBT) reduction capacity, a measure of superoxide anion production, but there was no apparent change in the GSH/glutathione disulfide (GSSG) ratio. Surprisingly, treatment of cells with low doses of 1-chloro-2, 4-dinitrobenzene (CDNB; 5 µM) or diethylmaleate (DEM; 0.5 mM), which transiently deplete GSH levels to about 40% of control levels, resulted in enhanced differentiation of HL-60 cells exposed to VD3 or all-trans-retinoic acid (ATRA), as well as under un-induced conditions (i.e., spontaneous differentiation). Enhanced differentiation occurred when cells were treated with the GSH-depleting agents 4 hours after treatment with differentiation inducers. These findings indicate that intracellular GSH levels are regulated in a complex fashion during HL-60 cell differentiation, and that transient GSH depletion using low doses of CDNB and DEM enhances the differentiation process.